STREM PBL with E-Authentic Assessment: Its Impact to Students’ Scientific Creativity on Static Fluid - Irma, Z. U.; Kusairi, S.; Yuliati, L. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to explore the scientific creativity of high school students on the static fluid in STREM PBL with an e-authentic assessment. This study used a mixed method with an embedded experimental design. This study involved 30 11th-grade senior high school students in Sidoarjo, Indonesia. Data collection techniques were carried out through pretest-posttest, interview, and observation. Pretest and posttest instruments consist of three scientific creativity essay questions with a reliability of 0.610. The results of the Wilcoxon test of p = .000, with the posttest being higher than the pretest, indicate a significant difference between students’ scientific creativity before and after learning. The effect size value of 0.87 indicates that STREM PBL with an e-authentic assessment moderately affects students’ scientific creativity. All indicators of scientific creativity have increased. The order of increasing the average scientific creativity score for each indicator is fluency (high) elaboration (moderate) originality (moderate) flexibility (moderate). Meanwhile, the order of the average level of scientific creativity at the posttest is fluency (very creative) elaboration (quite creative) = flexibility (quite creative) originality (less creative). Students’ scientific creativity increases because this learning makes students solve problems, carry out projects (design and create a product), carry out inquiry activities (experiment and investigation), collaborate with groups, and evaluate projects through self and peer assessment. Learning activities that can increase the level of fluency indicators are mentioning as many ideas as possible for experimental designs and product designs. Learning activities that can increase the level of flexibility indicators are integrating religion content into STEM (it is also better if integrating art content) and providing several problems and products from various fields. Learning activities that increase originality indicators give each individual or group a different project topic. Learning activities that can increase elaboration indicators are strengthening mastery of concepts and evaluating the work of oneself and others through self-assessment and peer assessment.